Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-03054-9
|View full text |Cite
|
Sign up to set email alerts
|

The proteome, not the transcriptome, predicts that oocyte superovulation affects embryonic phenotypes in mice

Abstract: Superovulation is the epitome for generating oocytes for molecular embryology in mice, and it is used to model medically assisted reproduction in humans. However, whether a superovulated oocyte is normal, is an open question. This study establishes for the first time that superovulation is associated with proteome changes that affect phenotypic traits in mice, whereas the transcriptome is far less predictive. The proteins that were differentially expressed in superovulated mouse oocytes and embryos compared to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 107 publications
1
15
0
Order By: Relevance
“…To distinguish between the possibilities, we compared the synthesis of ZP proteins against the abundance of ZP transcripts. Although the transcription of ZP genes is oocyte-specific and >95% of ZP3 mRNA is reportedly degraded during ovulation 2,26 , reanalysis of our previously generated RNAseq data 18 revealed that the ZP transcripts are in fact not as scarce in embryos as previously assumed. At the blastocyst stage, for example, the ZP transcripts populated the median region of the transcriptome distribution (Figure 2A).…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…To distinguish between the possibilities, we compared the synthesis of ZP proteins against the abundance of ZP transcripts. Although the transcription of ZP genes is oocyte-specific and >95% of ZP3 mRNA is reportedly degraded during ovulation 2,26 , reanalysis of our previously generated RNAseq data 18 revealed that the ZP transcripts are in fact not as scarce in embryos as previously assumed. At the blastocyst stage, for example, the ZP transcripts populated the median region of the transcriptome distribution (Figure 2A).…”
Section: Resultsmentioning
confidence: 64%
“… (a) . Genome-wide distribution of protein abundances (riBAQ) in zona-free oocytes, cleavage stages and blastocysts, based on the mass spectrometry dataset PXD012613 18 . The proteins ZP1, ZP2 and ZP3 populate, respectively, the 82 nd , 93 rd and 94 th percentile of the proteome distribution of oocytes, and the 80 th , 84 th and 84 th percentile of the proteome distribution of blastocysts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations